Controle da disseminação de vírus por meio de vetores na cultura da batata e caracterização molecular de três isolados atípicos de Potato vírus y (PVY) - Costa, Rejane Rodrigues da (2008)
In order to study the effect of insecticide treatments on virus spread by aphid vectors and on yield of two potato cultivars, a field experiment was carried out in Lavras-MG-Brazil, using randomized blocks, with 40 tubers for plot and four replicates. Potato tubers of Agata and Emeraude cultivars, with known virus incidence, were submitted to eight combinations of insecticide treatments, two treatments with insecticides plus fungicide Cabrio Top and two controls with no treatments. After the harvest were evaluated the virus incidence, yield and the insecticides residue in the potato tubers. Besides, three atypical isolates of the Potato virus Y (PVY) detected in Minas Gerais and Sao Paulo State-Brazil were also studied. It was accomplished through mechanical inoculation in species of Solonaceae, Amaranthaceae and Chenopodiaceae families, and through molecular characterization, identifying the PVY strain and performing the nucleotide and amino acid analysis of the coat protein gene. All the treatments with insecticides did not decrease the PVY spread in the field, showing that the insecticides are useless when seed potato with high virus incidence is used for sewing. The potato tubers submitted to all the treatments did not show any value of insecticides residue, higher than those allowed by ANVISA, suggesting that the concentration recommended by the manufacturer is safe for the consumer. The plants treated with Cabrio Top + Phorate on sewing presented higher yield when compared with the control and with other treatments. After mechanical inoculation, plants of Chenopodium quinoa, C. amaranticolor, Gomphrena globosa, Datura stramonium, Nicandra physaloides and Capsicum anuum cv. Florida VR2 were immune to all the three isolates. The other inoculated species, Physalis floridana, Nicotiana glutinosa, N. rustica e N. tabacum cvs. Havana, Turkish, Turkish NN e White burley, presented severe mosaic to PVY-AGA isolate and mild mosaic to PVY-AST and PVY-MON. Besides severe mosaic, the tobacco plants cvs. Turkish, Turkish NN and White Burley showed severe vein necrosis, dwarfing and death of old leaves when infected with PVY-AGA. The pepper cultivars, Yolo Y and Bastidon, showed the same mild mosaic when infected with the three virus isolates. The RT-PCR with specific primers allowed to obtain a 609 pb fragment for all the isolates, indicating that they were a variant of the necrotic strain of PVY, which causes tuber necrosis, named PVYNTN. The analysis of nucleotide sequence showed that the identity among the three studies PVY isolates had the same value, 96%. However, the identity of amino acids were different, being 96% only between the PVY-AGA and PVY-MON. The identity between PVY-AST and PVY-MON was 95% and between PVY-AGA and PVY-AST was 94%. Comparing the three studied PVY isolates with other 18 PVY isolates from GenBank the highest nucleotide identity (98%) was observed among PVY-AGA and three isolates from China and one from United States. The highest amino acid identity (98%) was maintained only between PVY-AGA and DQ157180 from USA, named NE-11. In the phylogenetic tree based on the nucleotide sequence, the isolates were located into two groups, and two main subgroups each. The Brazilian isolates were located on the same group, but PVY-AST and PVY-MON were in one subgroup and the PVY-AGA in another one, together with DQ157180. In the phylogenetic tree based on the amino acid sequence, the three Brazilian PVY isolates were displaced separately, but PVY-AGA still was closer to DQ157180 indicating its origin similarity. The PVY-AST isolate behaved as the common ancestor of all the PVY isolates which were analyzed.